YUYOS SETTINGS IN THE UPPER VALLEY OF CAÑETE RIVER: HUANGASCAR AND VIÑAC DISTRICTS - González Madueño, Consuelo (2004)
This paper is the result of an archeological survey that was conducted in the districts of Huangáscar y Viñac, located in the high basin of the Cañete river. The text starts with an introduction and definition of the studied area, as well as a summary of the previous research on the Yauyos ethnic group. Then, the results of the survey are presented, including data on architecture and ceramics of the sites of Huantanga, Viñaccancha, Huamani, Quencho, and Pucahuasi. Finally, an analysis of the mentioned settlements is presented, followed by a discussion about the relation between the archaeological data and the ethohistorical information about the Yauyos.